Cytotoxic Activities of Thiosemicarbazones and Their Metal Complexes - Rama Jyothi, N.; Mohammad Farook, N.A.; Cho, Migyung; Shim, Jaesool (Asian Journal of Chemistry, 2013)
The cytotoxic properties of thiosemicarbazones and their transition metal complexes are reviewed since 2006.